Implementation of Village Autonomy in Development at Muara Pagatan Village, Kusan Hilir District, Tanah Bumbu Regency - Abdul Sukur; Budi Suryadi; Muhammad Riduansyah Syafari (Socio-Economic and Humanistic Aspects for Township and Industry, 2025)
The village government plays an important role in formulating and implementing policies that are in line with the potential and needs of the local community. The purpose of this study is to determineimplementation of Village Autonomy in the field of infrastructure development in Muara Pagatan Village, Kusan Hilir District and to find out the implementation of Village Autonomy in the field of Health in Muara Pagatan Village, Kusan Hilir District and to find out the Supporting and Inhibiting Factors of the implementation of village autonomy in the field of Infrastructure and Health development. The results of this study are that the implementation of village autonomy in the field of infrastructure development in Muara Pagatan Village shows the effectiveness of decentralization and community empowerment in improving local welfare